Selênio orgânico na alimentação de matrizes de tilápia-do-Nilo (Oreochromis niloticus) - Pereira, Thiago Scremin; Perez Fabregat, Thiago El Hadi; Kochenborger Fernandes, Joao Batista; Boscolo, Camila Nomura; Alvarado Castillo, Julian David; Ribeiro Dias Koberstein, Teresa Cristina (Universidade Estadual de Maringa, 2009)
Organic selenium in the diet of Nile tilapia (Oreochromis niloticus) broodstock. The aim of this study to test the effect of organic selenium supplementation in the diets of Nile tilapia broodstock. Growth, reproductive performance and performance of fingerlings were evaluated. Eighty adult fish were used, with average weight of 121.7 g and divided into groups of four animals (3 female and 1 male) stocked in 20 tanks with 1.5 cubic meters. The fish were fed five diets containing different levels of organic selenium (0.0, 0.25, 0.50, 0.75, and 1.0 mg kg-1 ration). In the experimental period, females from all tanks were captured and the eggs collected. The experimental design was entirely randomized, with five treatments and four replicates. To evaluate progeny performance, the fingerlings were shared in four aquariums and fed during 30 days with commercial diet (45% CP). The supplementation with organic selenium did not affect the productive performance as with the reproductive parameters of the broodstock (p > 0.05). on the other hand, the broodstock fed with 0.50 mg of organic selenium produced fingerlings that presented improved weight gain (p < 0.05) compared to fish fed the control diet.
Organic selenium in the diet of Nile tilapia (Oreochromis niloticus) broodstock.